2012
DOI: 10.21608/jappmu.2012.82938
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Trends for Some Milk Yield Traits of Egyptian Buffaloes

Abstract: A total number of 600 female buffaloes, having 3321 lactation records, from first to tenth parity, kept at three experimental farms (Mahalet Mousa, El-Nataf El-Gaded and El-Nataf El-Kadem), belonging to the Animal Production Research Institute, Ministry of Agriculture, Cairo, Egypt, during the period from 2000 to 2007 were used to study genetic and phenotypic progress, achieved by the Mixed Model Equations (MME) for the Best Liner Unbiased Prediction. The number of sires were 66 sires and the average number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 7 publications
3
8
3
Order By: Relevance
“…The alike phenotypic trend for FDO was non-significant, but positive, which is not desirable. Similarly, noticed by El-Arian et al (2012) for MY, LP and DO in Friesian cows. In Egyptian buffaloes, Fooda et al (2010) obtained the annual phenotypic trend for milk yield was 26 kg being in all Mahallet Mousa farms.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The alike phenotypic trend for FDO was non-significant, but positive, which is not desirable. Similarly, noticed by El-Arian et al (2012) for MY, LP and DO in Friesian cows. In Egyptian buffaloes, Fooda et al (2010) obtained the annual phenotypic trend for milk yield was 26 kg being in all Mahallet Mousa farms.…”
Section: Resultssupporting
confidence: 74%
“…Fooda et al (2010) found the annual genetic trends for milk yield in all Mahallet Mousa farms were positive and being 0.58 kg in Egyptian buffaloes. El-Arian et al (2012) obtained that the annual genetic change for TMY and LP was positive and being 3.70kg and 0.55d, respectively as the regression coefficient of sire breeding values per year in Egyptian buffaloes. Annual phenotypic trends for studied traits in Egyptian buffaloes are illustrated in Table 6.…”
Section: Resultsmentioning
confidence: 96%
“…The obtained results were in the same line of those obtained by (Thevamanoharan et al, 2002), (Mourad and Khattab, 2009), (El-Bramony, 2011), (Malhado et al, 2013) and (El-Bramony, 2014). On the contrary to the present findings (Kawthar et al, 2005), (EL-Arian et al, 2012) and (Ibrahim et al, 2012) showed high heritability for days in milk and milk yield. Moderate heritability estimate was 0.18 and 0.19 for days open and calving interval, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…High positive genetic correlation between total milk yield with each of days in milk (0.73) and 305day milk yield (0.86). Similar to present results (Mourad and Khattab, 2009), (Ibrahim et al, 2012), (EL-Arian et al, 2012) and (Shalaby et al, 2013) recorded that high positive genetic correlation between days in milk and milk yield. The opposite results obtained by (Barros et al, 2016) reported that low negative correlation between days in milk and milk yield.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation